Analisis Situasi Masalah Kesehatan Penyakit Tidak Menular di Kota Depok Tahun 2023 - Simanjuntak, Elvi Nora; Adisasmita, Asri, Prof; Djajuli, Hidayat Nuh Ghazali (UI Scholars Hub, 2024)
Indonesia faces one of the biggest health challenges stemming from non-communicable diseases (degenerative diseases). The incidence of this health problem has shone a spotlight on the international community of both modern and traditional societies in all parts of the world. The shift in lifestyle from traditional to modern living is one of the factors that has led to the high number of degenerative disease cases in Indonesia. Currently, the number of people sickened by these non-communicable diseases continues to increase even at a young age with stroke, heart disease, and diabetes. Depok City as one of the cities that has experienced rapid progress is also a concern by the local government for the high prevalence of non-communicable diseases among the community. With this health problem, it is important to take action in analyzing the situation of the health problem so that it can determine health priorities, especially non-communicable diseases. This activity uses descriptive observational research methods using qualitative and quantitative data. Determination of the main health problems with respondents, namely the Head of Division at the Health Office and the Head of Puskesmas at each selected health center with a total of twenty-three respondents. Scoring and ranking using the PAHO adopted Hanlon method based on the Basic Prioriy Rating (BPR). Through the results of the ranking order, the results of problem identification obtained nine health problems in non-communicable diseases, namely, Hypertension, Diabetes Mellitus, People with Mental Disorders, Chronic Renal Failure, Coronary Heart Disease, Pre-eclampsia Hypertension, Traffic Accidents, and Cancer. The results of the assessment of health problems with BPR scores placed the top three priority health problems in non-communicable diseases as Hypertension (38.69). Stunting (37.87), and Pre-eclampsia Hypertension (32.10) in Depok City.